Design of a software architecture for Velocimetry Systems - Nunes, Roger Pizzato (2007)
The physical systems in the area of fluid mechanics present a complex behavior and, in certain regimes, they have not been completely described and understood by the physics laws yet. For this reason, the experimental techniques employed for the velocity field measurement of a given fluid flow still play an important hole. It is critical in Engineering, a knowledge area in which it is necessary to project, to implement, or to validate a prototype that involves such physical concepts. In the last ten years, the technological advance in the areas of microelectronics, optics and computer science allowed that image processing techniques were applied to the analysis of fluid flows. These techniques have propitiated that much more qualitative and quantitative information could have been extracted from the fluid flow. As a consequence, a better and a more accurate characterization of the physical phenomena became possible, enabling the validation of the developed models. In this context, the main objective of this work is to show the architecture of a computational tool for the measurement of the twodimensional velocity field of fluid flows through digital image processing. This tool has been applied in different physical systems in fluid mechanics, providing great results as our recent publications show.